Preparation method of antistatic and antibacterial modified polypropylene particles

Through the combination technology of hydroxylated 3-bromo-4-vinylpyrphine, polypropylene block copolymer and flame oxidized carbon nanotube-loaded nanosilver, the electrostatic and antibacterial problems of polypropylene plastics are solved, and long-term anti-static are achieved and the improvement of antibacterial properties enhances the stability and durability of the material.

CN119264553AActive Publication Date: 2025-01-07JIANGSU SONGSHANG TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411387573.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-05
Publication Date
2025-01-07
Estimated Expiration
2044-10-05

AI Technical Summary

Technical Problem

Polypropylene plastics are prone to static electricity, resulting in vacuum absorption, electric shock, combustion and explosion. Antibacterial materials are needed in the fields of medical care, and the prior art is difficult to achieve both antistatic and antibacterial effects.

Method used

Hydroxylated 3-bromo-4-vinylpyridine reacts with end carboxylic polypropylene to form an amphiphilic block copolymer, and the multi-wall carbon nanotubes are treated with flame oxidation, and nanosilver loaded with annealing treatment is formed. The conductive layer and micro interface achieve antistatic and antibacterial properties.

Benefits of technology

Long-term antistatic and antibacterial properties are achieved, the stability and durability of the material are enhanced, and the static hazards and bacterial infection are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of antistatic and antibacterial modified polypropylene particles, and relates to the technical field of high polymer materials. According to the invention, hydroxylation of a terminal group of 3-bromo-4-vinylpyridine is realized by using hydrogen peroxide, so that esterification reaction with carboxyl-terminated polypropylene is carried out, an amphiphilic block copolymer is formed, quaternization is realized through bromoethane, antibacterial and antistatic properties are realized, blending modification is carried out on polypropylene, long-acting antibacterial and antistatic effects are realized, and the antibacterial and antistatic polypropylene composite material is prepared. Multi-walled carbon nanotubes are modified through instantaneous oxidation flames, so that the multi-walled carbon nanotubes interact with silver ions, the antistatic and antibacterial performance is improved, a polypropylene matrix is filled with the multi-walled carbon nanotubes, annealing treatment is conducted, dispersion of filler in the matrix is promoted, meanwhile, the stability of the whole system is enhanced through pressurization, and the antistatic and antibacterial durability is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a method for preparing antistatic and antibacterial modified polypropylene particles. Background Art

[0002] Polypropylene (PP) is a colorless, odorless, non-toxic, translucent thermoplastic general-purpose plastic made by propylene polymerization. Due to its practicality and economy, it has now developed into the world's second largest thermoplastic resin and has been widely used in the automotive, home appliance, packaging, medical, fiber and building materials industries. One of the biggest defects of ordinary PP is that it is very easy to generate static electricity. Due to the non-polar structure and excellent electrical insulation properties of polypropylene, static electricity is very easy to accumulate on its surface during industrial production and application, resulting in dust absorption, electric shock, combustion and even explosion, which brings harm to industrial and agricultural production and daily life. According to relevant research, static electricity is one of the main causes of fire and explosion. The losses caused by static electricity in the world are as high as billions of dollars each year.

[0003] Therefore, how to reduce and eliminate the electrostatic hazards of polypropylene plastics and their products has become a technical issue that needs to be solved urgently. At the same time, with the development of plastic modification technology, polypropylene is widely used in food packaging, textiles, biomedicine, medical equipment and other fields, which require the avoidance of bacterial infection and disease transmission. And as the awareness of healthy consumption gradually takes root in people's hearts, the market prospects of plastic products such as antibacterial polypropylene are broad. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing antistatic and antibacterial modified polypropylene particles to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing antistatic and antibacterial modified polypropylene particles, comprising the following preparation steps:

[0006] (1) Deionized water is heated to 78-90°C, and hydrogen peroxide and 3-bromo-4-vinylpyridine are added dropwise at the same time, reacted at 80°C for 2.5-4 hours, cooled to room temperature, first dissolved with methanol, then precipitated with anhydrous ether, the supernatant is discarded, and vacuum dried at 60°C for 18-30 hours to obtain hydroxylated 3-bromo-4-vinylpyridine;

[0007] (2) The molecular weight is 4×10 3 The carboxyl-terminated polypropylene and hydroxylated 3-bromo-4-vinylpyridine are dissolved in cyclohexanone, 2-chloro-1-methyl iodine and triethylamine are added, the temperature is raised to 120°C, the reaction is performed for 8.5 to 11 hours, the solid is cooled to room temperature, filtered, and the solid is extracted with methanol as an extractant for 40 to 60 hours, and vacuum dried at 60°C for 18 to 30 hours to obtain a block copolymer;

[0008] (3) The block copolymer was dissolved in cyclohexanone, ethyl bromide was added, refluxed for 4 h, filtered, the solid was taken, dried at 60 °C for 5-10 h, and a 9×10 4 Polypropylene and xylene are heated to 80-110°C, stirred at 30-70 rpm for 30-50 min, and dried at 120°C for 2-5 h to obtain modified polypropylene;

[0009] (4) subjecting the multi-walled carbon nanotubes to instantaneous oxidation flame treatment at a flame temperature of 1500 to 2800° C., then adding a 10 wt% sodium potassium tartrate aqueous solution of 50 to 100 times the mass of the multi-walled carbon nanotubes, ultrasonicating at 21 kHz for 8 to 15 min, heating to 40° C., stirring at 60 to 120 rpm for 20 to 40 min, adding a silver ammonia solution of 5 to 10 times the mass of the multi-walled carbon nanotubes dropwise at 4 mL / min, continuing to stir for 10 to 20 min, washing with deionized water for 3 to 8 times, and vacuum drying at 70° C. for 10 to 15 h to obtain carbon nanotubes loaded with nanosilver;

[0010] (5) The carbon nanotube-loaded nanosilver and modified polypropylene are mixed in a mass ratio of 10:0.5-1.5, heated to 170-188° C., melt blended at a speed of 15-30 rpm for 10-20 min, and then annealed and extruded to obtain antistatic and antibacterial modified polypropylene particles.

[0011] Furthermore, the dripping rate in step (1) is 1 to 3 mL / min.

[0012] Furthermore, in step (1), the mass ratio of deionized water, hydrogen peroxide and 3-bromo-4-vinylpyridine is 15:8-11:2.5-3.5.

[0013] Furthermore, the molecular weight in step (2) is 4×10 3 Preparation method of carboxyl-terminated polypropylene: 4 The polypropylene and 95wt% nitric acid aqueous solution are mixed in a mass ratio of 1:4, heated to 110°C for reflux, stirred at 150-300rpm for 8h, cooled to room temperature, washed with water and acetone in turn until the pH of the washing solution is 6, and dried at 50-80°C for 7-10h to obtain the product.

[0014] Furthermore, the molecular weight in step (2) is 4×10 3 The mass ratio of carboxyl-terminated polypropylene, hydroxylated 3-bromo-4-vinylpyridine, cyclohexanone, 2-chloro-1-methyliodopyridine and triethylamine is 1:2-3:50:2-3:2.

[0015] Furthermore, in step (3), the block copolymer, cyclohexanone, ethyl bromide, and molecular weight are 9×10 4The mass ratio of polypropylene and xylene is 0.3:6:0.6:8~10:50~100.

[0016] Furthermore, the preparation method of the silver ammonia solution in step (4) is as follows: 2wt% silver nitrate aqueous solution and 2wt% ammonia aqueous solution are mixed in a mass ratio of 1:0.5, and then the pH value of the solution is adjusted to 11 with ammonia water, the temperature is raised to 35-45°C, and the mixture is mixed evenly.

[0017] Furthermore, the vacuum degree of the vacuum drying in step (1), step (2) and step (4) is 0.2 to 1 kPa.

[0018] Furthermore, the annealing process parameters of step (5) are as follows: temperature of 120-180° C., pressure of 270-370 MPa, and time of 80-150 min.

[0019] Furthermore, the process parameters of the extrusion granulation in step (5) are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the temperatures of the three sections and the die are 170, 180, 200, and 220° C. respectively, and the shear rate is 80 to 150 rpm.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The modified polypropylene particles of the invention are firstly prepared by modifying polypropylene with an amphiphilic block copolymer, then filled with carbon nanotubes loaded with nanosilver, and finally annealed to achieve antibacterial and antistatic effects.

[0022] Firstly, hydrogen peroxide is used to initiate 3-bromo-4-vinylpyridine to cause free radical polymerization, and at the same time, its terminal groups are oxidized to achieve hydroxylation. Then, an esterification reaction occurs with double-terminal carboxyl low-molecular-weight polypropylene, and a chain segment of 3-bromo-4-vinylpyridine is introduced into the main chain of the polypropylene to form an amphiphilic block copolymer. Ethyl bromide is used to react with the nitrogen atom on the pyridine ring in the 3-bromo-4-vinylpyridine chain segment to generate a quaternary ammonium salt, thereby achieving antibacterial and antistatic properties of the matrix. Thus, the polypropylene is blended and modified. Due to the presence of the polypropylene chain segment, the macromolecular modifier is difficult to separate from the matrix, thereby achieving long-term antibacterial properties. In addition, during the processing, the macromolecular modifier is enriched and arranged on the side facing the air, and a continuous and uniform conductive layer is formed on the surface of the matrix by absorbing moisture and its own ions, thereby achieving long-term antistatic properties.

[0023] Secondly, flame heat treatment is used to modify the surface of multi-walled carbon nanotubes. Through instantaneous high-temperature oxidation flame, low molecular weight, oil stains and weak interface layers adsorbed on the surface are removed, so that a large number of free radicals and ions are generated on the surface, and then polar groups are formed, which interact with silver ions to load nanosilver particles. The two contact each other to form a tunnel effect, enhance the conductivity of the matrix, and improve the antistatic and antibacterial properties. Then, it is filled in a polypropylene matrix and annealed. At a higher annealing temperature, the molecular chains of some amorphous regions in polypropylene gradually thaw over time, and the solid chains slip and spirally form crystalline chains, so that the molecular chains in the amorphous region have stronger mobility and rearrangement and crystallization, thereby promoting good dispersion of the filler in the polypropylene matrix and forming a smaller micro-interface to achieve long-term antistatic and antibacterial properties. At the same time, by pressurizing, the bromine atoms on 3-bromo-4-vinylpyridine are decomposed, thereby enhancing the antibacterial property of the matrix. At the same time, the system density is increased, the molecular chain spacing is reduced, the nanofiller is fixed, the stability of the entire system is enhanced, and the antistatic and antibacterial durability is further improved. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the antistatic and antibacterial modified polypropylene particles prepared in the following examples are as follows:

[0026] The antistatic and antibacterial modified polypropylene particles were hot pressed at 150°C to form a film with a thickness of 500 μm.

[0027] Antibacterial property: Take the embodiment and comparative example of the same size and refer to GB / T21510 to test the antibacterial rate, and let it stand for 60 days, and then test its antibacterial rate again.

[0028] Antistatic: Take the embodiment and comparative example of the same size and refer to GB1410, detect the surface resistivity, let it stand for 60 days, and then detect its surface resistivity again.

[0029] Example 1; (1) Deionized water was heated to 78°C, and hydrogen peroxide and 3-bromo-4-vinyl pyridine were added dropwise at 1 mL / min, reacted at 80°C for 2.5 h, cooled to room temperature, first dissolved with methanol, then precipitated with anhydrous ether, the supernatant was discarded, and dried at 60°C and a vacuum degree of 0.2 kPa for 18 h to obtain hydroxylated 3-bromo-4-vinyl pyridine; the mass ratio of deionized water, hydrogen peroxide, and 3-bromo-4-vinyl pyridine was 15:8:2.5;

[0030] (2) The molecular weight is 9×10 4 The polypropylene and 95wt% nitric acid aqueous solution were mixed in a mass ratio of 1:4, heated to 110℃ and refluxed, stirred at 150rpm for 8h, cooled to room temperature, washed with water and acetone in turn until the pH of the washing solution was 6, and dried at 50℃ for 7h to obtain a molecular weight of 4×10 3 The carboxyl-terminated polypropylene has a molecular weight of 4×10 3 The carboxyl-terminated polypropylene and hydroxylated 3-bromo-4-vinylpyridine were dissolved in cyclohexanone, 2-chloro-1-methyl iodine and triethylamine were added, the temperature was raised to 120°C, the reaction was performed for 8.5 hours, the mixture was cooled to room temperature, filtered, the solid was taken, and methanol was used as an extractant for 40 hours, and the block copolymer was obtained by drying at 60°C and a vacuum degree of 0.2 kPa for 18 hours; the molecular weight was 4×10 3 The mass ratio of carboxyl-terminated polypropylene, hydroxylated 3-bromo-4-vinylpyridine, cyclohexanone, 2-chloro-1-methyliodopyridine, and triethylamine is 1:2:50:2:2;

[0031] (3) The block copolymer was dissolved in cyclohexanone, ethyl bromide was added, refluxed for 4 h, filtered, the solid was taken, dried at 60 °C for 5 h, and a 9×10 4 polypropylene and xylene, heated to 80°C, stirred at 30rpm for 30min, and dried at 120°C for 2h to obtain modified polypropylene; the block copolymer, cyclohexanone, ethyl bromide, molecular weight 9×10 4 The mass ratio of polypropylene and xylene is 0.3:6:0.6:8:50;

[0032] (4) 2 wt % silver nitrate aqueous solution and 2 wt % ammonia aqueous solution were mixed in a mass ratio of 1:0.5, and then the pH of the solution was adjusted to 11 with ammonia water, and the temperature was raised to 35° C. and mixed to obtain a silver ammonia solution; multi-walled carbon nanotubes were subjected to instantaneous oxidation flame treatment, and the flame temperature was 1500° C., and then 10 wt % potassium sodium tartrate aqueous solution of 50 times the mass of the multi-walled carbon nanotubes was added, 21 kHz ultrasound was applied for 8 min, the temperature was raised to 40° C., and the silver ammonia solution of 5 times the mass of the multi-walled carbon nanotubes was added dropwise at 4 mL / min, and the stirring was continued for 10 min, and the solution was washed with deionized water for 3 times, and dried at 70° C. and a vacuum degree of 0.2 kPa for 10 h to obtain carbon nanotubes loaded with nanosilver;

[0033] (5) Carbon nanotubes loaded with nanosilver and modified polypropylene were mixed in a mass ratio of 10:0.5, heated to 170°C, melt blended at a speed of 15 rpm for 10 min, then annealed at a temperature of 120°C and a pressure of 270 MPa for 80 min, and then extruded into granules. The process parameters were as follows: screw diameter of 20 mm, aspect ratio of 25:1, three-stage and die temperatures of 170, 180, 200, and 220°C, respectively, and a shear rate of 80 rpm, to obtain antistatic and antibacterial modified polypropylene granules.

[0034] Example 2; (1) deionized water was heated to 82°C, and hydrogen peroxide and 3-bromo-4-vinyl pyridine were added dropwise at 2 mL / min, reacted at 80°C for 3 h, cooled to room temperature, first dissolved with methanol, then precipitated with anhydrous ether, the supernatant was discarded, and dried at 60°C and a vacuum degree of 0.5 kPa for 24 h to obtain hydroxylated 3-bromo-4-vinyl pyridine; the mass ratio of deionized water, hydrogen peroxide, and 3-bromo-4-vinyl pyridine was 15:9.5:3;

[0035] (2) The molecular weight is 9×10 4 The polypropylene and 95wt% nitric acid aqueous solution were mixed in a mass ratio of 1:4, heated to 110℃ and refluxed, stirred at 230rpm for 8h, cooled to room temperature, washed with water and acetone in turn until the pH of the washing solution was 6, and dried at 65℃ for 8h to obtain a molecular weight of 4×10 3 The carboxyl-terminated polypropylene has a molecular weight of 4×10 3 The carboxyl-terminated polypropylene and hydroxylated 3-bromo-4-vinylpyridine were dissolved in cyclohexanone, 2-chloro-1-methyl iodine and triethylamine were added, the temperature was raised to 120°C, the reaction was carried out for 9 hours, the mixture was cooled to room temperature, filtered, the solid was taken, and methanol was used as an extractant for 50 hours, and the block copolymer was obtained by drying at 60°C and a vacuum degree of 0.5 kPa for 24 hours; the molecular weight was 4×10 3The mass ratio of carboxyl-terminated polypropylene, hydroxylated 3-bromo-4-vinylpyridine, cyclohexanone, 2-chloro-1-methyliodopyridine, and triethylamine is 1:2.5:50:2.5:2;

[0036] (3) The block copolymer was dissolved in cyclohexanone, ethyl bromide was added, refluxed for 4 h, filtered, the solid was taken, dried at 60 °C for 7 h, and a 9×10 4 polypropylene and xylene, heated to 90°C, stirred at 50rpm for 40min, and dried at 120°C for 4h to obtain modified polypropylene; the block copolymer, cyclohexanone, ethyl bromide, molecular weight 9×10 4 The mass ratio of polypropylene and xylene is 0.3:6:0.6:9:75;

[0037] (4) 2 wt % silver nitrate aqueous solution and 2 wt % ammonia aqueous solution were mixed in a mass ratio of 1:0.5, and then the pH of the solution was adjusted to 11 with ammonia water, and the temperature was raised to 40° C. and mixed to obtain a silver ammonia solution; multi-walled carbon nanotubes were subjected to instantaneous oxidation flame treatment, and the flame temperature was 2200° C., and then 10 wt % potassium sodium tartrate aqueous solution of 75 times the mass of the multi-walled carbon nanotubes was added, 21 kHz ultrasound was applied for 11 min, the temperature was raised to 40° C., and the mixture was stirred at 90 rpm for 30 min. The silver ammonia solution of 8 times the mass of the multi-walled carbon nanotubes was added dropwise at 4 mL / min, and the stirring was continued for 15 min. The mixture was washed with deionized water for 5 times, and dried at 70° C. and a vacuum degree of 0.5 kPa for 12 h to obtain carbon nanotubes loaded with nanosilver;

[0038] (5) Carbon nanotubes loaded with nanosilver and modified polypropylene were mixed in a mass ratio of 10:1, heated to 180°C, melt blended at a speed of 20 rpm for 15 min, then annealed at a temperature of 150°C and a pressure of 320 MPa for 110 min, and then extruded into granules. The process parameters were as follows: screw diameter of 20 mm, aspect ratio of 25:1, three-stage and die temperatures of 170, 180, 200, and 220°C, respectively, and a shear rate of 110 rpm, to obtain antistatic and antibacterial modified polypropylene granules.

[0039] Example 3; (1) heating deionized water to 90°C, and simultaneously adding hydrogen peroxide and 3-bromo-4-vinylpyridine at 3 mL / min, reacting at 80°C for 4 h, cooling to room temperature, first dissolving with methanol, then precipitating with anhydrous ether, discarding the supernatant, and drying at 60°C and a vacuum degree of 1 kPa for 30 h to obtain hydroxylated 3-bromo-4-vinylpyridine; the mass ratio of deionized water, hydrogen peroxide, and 3-bromo-4-vinylpyridine is 15:11:3.5;

[0040] (2) The molecular weight is 9×10 4The polypropylene and 95wt% nitric acid aqueous solution were mixed in a mass ratio of 1:4, heated to 110℃ and refluxed, stirred at 300rpm for 8h, cooled to room temperature, washed with water and acetone in turn until the pH of the washing solution was 6, and dried at 80℃ for 10h to obtain a molecular weight of 4×10 3 The carboxyl-terminated polypropylene has a molecular weight of 4×10 3 The carboxyl-terminated polypropylene and hydroxylated 3-bromo-4-vinylpyridine were dissolved in cyclohexanone, 2-chloro-1-methyl iodine and triethylamine were added, the temperature was raised to 120°C, the reaction was carried out for 11 hours, the mixture was cooled to room temperature, filtered, the solid was taken, and methanol was used as an extractant for 60 hours, and the block copolymer was dried at 60°C and a vacuum degree of 1 kPa for 30 hours. The molecular weight was 4×10 3 The mass ratio of carboxyl-terminated polypropylene, hydroxylated 3-bromo-4-vinylpyridine, cyclohexanone, 2-chloro-1-methyliodopyridine, and triethylamine is 1:3:50:3:2;

[0041] (3) The block copolymer was dissolved in cyclohexanone, ethyl bromide was added, refluxed for 4 h, filtered, the solid was taken, dried at 60 °C for 10 h, and a 9×10 4 polypropylene and xylene, heated to 110°C, stirred at 70rpm for 50min, and dried at 120°C for 5h to obtain modified polypropylene; the block copolymer, cyclohexanone, ethyl bromide, molecular weight 9×10 4 The mass ratio of polypropylene and xylene is 0.3:6:0.6:10:100;

[0042] (4) 2 wt % silver nitrate aqueous solution and 2 wt % ammonia aqueous solution were mixed in a mass ratio of 1:0.5, and then the pH of the solution was adjusted to 11 with ammonia water, and the temperature was raised to 45° C. and mixed to obtain a silver ammonia solution; multi-walled carbon nanotubes were subjected to instantaneous oxidation flame treatment, the flame temperature was 2800° C., and then 10 wt % potassium sodium tartrate aqueous solution of 100 times the mass of the multi-walled carbon nanotubes was added, 21 kHz ultrasound was applied for 15 min, the temperature was raised to 40° C., and the mixture was stirred at 120 rpm for 40 min. The silver ammonia solution of 10 times the mass of the multi-walled carbon nanotubes was added dropwise at 4 mL / min, and the stirring was continued for 20 min. The mixture was washed with deionized water for 8 times, and dried at 70° C. and a vacuum degree of 1 kPa for 15 h to obtain carbon nanotubes loaded with nanosilver;

[0043] (5) Carbon nanotubes loaded with nanosilver and modified polypropylene were mixed in a mass ratio of 10:1.5, heated to 188°C, melt blended at a speed of 30 rpm for 20 min, then annealed at a temperature of 180°C and a pressure of 370 MPa for 150 min, and then extruded into granules. The process parameters were as follows: screw diameter of 20 mm, aspect ratio of 25:1, three-stage and die temperatures of 170, 180, 200, and 220°C, respectively, and a shear rate of 150 rpm, to obtain antistatic and antibacterial modified polypropylene granules.

[0044] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (2) is different, and step (2) is changed to: 4 The polypropylene and 95wt% nitric acid aqueous solution were mixed in a mass ratio of 1:4, heated to 110℃ and refluxed, stirred at 230rpm for 8h, cooled to room temperature, washed with water and acetone in turn until the pH of the washing solution was 6, and dried at 65℃ for 8h to obtain a molecular weight of 4×10 3 The carboxyl-terminated polypropylene has a molecular weight of 4×10 3 The carboxyl-terminated polypropylene and hydroxylated 3-bromo-4-vinylpyridine were dissolved in cyclohexanone, triethylamine was added, the temperature was raised to 120°C, the reaction was carried out for 9 hours, the mixture was cooled to room temperature, filtered, the solid was taken, and methanol was used as an extractant for 50 hours, and the block copolymer was obtained by drying at 60°C and a vacuum degree of 0.5 kPa for 24 hours. The molecular weight was 4×10 3 The mass ratio of carboxyl-terminated polypropylene, hydroxylated 3-bromo-4-vinylpyridine, cyclohexanone and triethylamine is 1:2.5:50:2; the remaining steps are the same as those in Example 2.

[0045] Comparative Example 2; The difference between Comparative Example 2 and Example 2 is that there is no step (1), step (2) and step (3); the remaining steps are the same as Example 2.

[0046] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (4) is different. Step (4) is changed to: 2wt% silver nitrate aqueous solution and 2wt% ammonia aqueous solution are mixed in a mass ratio of 1:0.5, and then the pH of the solution is adjusted to 11 with ammonia water, the temperature is raised to 40°C, and mixed to obtain a silver ammonia solution; multi-walled carbon nanotubes are mixed with 10wt% potassium sodium tartrate aqueous solution with a mass of 75 times that of the multi-walled carbon nanotubes, ultrasonicated at 21kHz for 11min, heated to 40°C, stirred at 90rpm for 30min, and 8 times the mass of the multi-walled carbon nanotubes The silver ammonia solution is added dropwise at 4mL / min, and stirring is continued for 15min, washed with deionized water 5 times, and dried at 70°C and a vacuum degree of 0.5kPa for 12h to obtain carbon nanotubes loaded with nanosilver; the remaining steps are the same as in Example 2.

[0047] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (4) is different. Step (4) is changed to: subjecting the multi-walled carbon nanotubes to instantaneous oxidation flame treatment at a flame temperature of 2200°C, washing them with deionized water 5 times, and drying them at 70°C and a vacuum degree of 0.5 kPa for 12 h to obtain modified carbon nanotubes; the remaining steps are the same as in Example 2.

[0048] Comparative Example 5; The difference between Comparative Example 5 and Example 2 is that step (5) is different. Step (5) is changed to: annealing the modified polypropylene at a temperature of 150° C. and a pressure of 320 MPa for 110 min, and then extruding and granulating. The process parameters are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the temperatures of the three sections and the die are 170, 180, 200, and 220° C., respectively, and the shear rate is 110 rpm to obtain antistatic and antibacterial modified polypropylene particles; the remaining steps are the same as in Example 2.

[0049] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that step (5) is different. Step (5) is changed to: carbon nanotubes loaded with nanosilver and modified polypropylene are mixed in a mass ratio of 10:1, heated to 180°C, melt blended at a speed of 20 rpm for 15 min, then annealed at a temperature of 150°C for 110 min, and then extruded into granules. The process parameters are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the temperatures of the three sections and the die are 170, 180, 200, and 220°C, respectively, and the shear rate is 110 rpm, to obtain antistatic and antibacterial modified polypropylene particles; the remaining steps are the same as in Example 2.

[0050] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that step (5) is different. Step (5) is changed to: carbon nanotubes loaded with nanosilver and modified polypropylene are mixed in a mass ratio of 10:1, heated to 180°C, melt blended at a speed of 20 rpm for 15 min, and then extruded into granules. The process parameters are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the temperatures of the three sections and the die are 170, 180, 200, and 220°C, respectively, and the shear rate is 110 rpm, to obtain antistatic and antibacterial modified polypropylene particles; the remaining steps are the same as in Example 2.

[0051] Effect example

[0052] Table 1 below shows the performance analysis results of the antistatic and antibacterial modified polypropylene particles of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.

[0053] Table 1

[0054]

[0055] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses hydrogen peroxide to initiate and oxidize 3-bromo-4-vinylpyridine to achieve hydroxylation of its terminal groups, and then reacts with low-molecular-weight polypropylene with double-terminal carboxyl groups to form an amphiphilic block copolymer, and quaternization is achieved by ethyl bromide, thereby achieving antibacterial and antistatic properties of the matrix, thereby blending and modifying the polypropylene. Due to the presence of the polypropylene chain segment, the macromolecular modifier is difficult to separate from the matrix, achieving long-term antibacterial properties, and during the processing, it is enriched and arranged on the side facing the air, forming a continuous and uniform conductive layer on the surface of the matrix, achieving long-term antistatic properties, and then, flame heat treatment is used to modify the surface of the multi-walled carbon nanotubes, and the instantaneous high temperature The oxidizing flame generates a large number of free radicals and ions on the surface, which then form polar groups and interact with silver ions to load nanosilver particles. The two contact each other to form a tunnel effect, which enhances the antistatic and antibacterial properties. Then, it is filled in a polypropylene matrix and annealed. At a higher annealing temperature, the molecular chain mobility in the amorphous region is stronger, and rearrangement crystallization occurs, thereby promoting good dispersion of the filler in the polypropylene matrix and forming a smaller micro-interface to achieve long-term antistatic and antibacterial properties. At the same time, by pressurizing, the bromine atoms on 3-bromo-4-vinylpyridine are decomposed, thereby enhancing the antibacterial property of the matrix. At the same time, the stability of the entire system is enhanced, and the durability of antistatic and antibacterial properties is further improved.

[0056] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing antistatic and antibacterial modified polypropylene particles, characterized in that: The method comprises the following preparation steps: (1) Deionized water is heated to 78-90°C, and hydrogen peroxide and 3-bromo-4-vinylpyridine are added dropwise at the same time, reacted at 80°C for 2.5-4 hours, cooled to room temperature, first dissolved with methanol, then precipitated with anhydrous ether, the supernatant is discarded, and vacuum dried at 60°C for 18-30 hours to obtain hydroxylated 3-bromo-4-vinylpyridine; (2) The molecular weight is 4×10 3 The carboxyl-terminated polypropylene and hydroxylated 3-bromo-4-vinylpyridine are dissolved in cyclohexanone, 2-chloro-1-methyl iodine and triethylamine are added, the temperature is raised to 120°C, the reaction is performed for 8.5 to 11 hours, the solid is cooled to room temperature, filtered, and the solid is extracted with methanol as an extractant for 40 to 60 hours, and vacuum dried at 60°C for 18 to 30 hours to obtain a block copolymer; (3) The block copolymer was dissolved in cyclohexanone, ethyl bromide was added, refluxed for 4 h, filtered, the solid was taken, dried at 60 °C for 5-10 h, and a 9×10 4 Polypropylene and xylene are heated to 80-110°C, stirred at 30-70 rpm for 30-50 min, and dried at 120°C for 2-5 h to obtain modified polypropylene; (4) subjecting the multi-walled carbon nanotubes to instantaneous oxidation flame treatment at a flame temperature of 1500 to 2800° C., then adding a 10 wt% sodium potassium tartrate aqueous solution of 50 to 100 times the mass of the multi-walled carbon nanotubes, ultrasonicating at 21 kHz for 8 to 15 min, heating to 40° C., stirring at 60 to 120 rpm for 20 to 40 min, adding a silver ammonia solution of 5 to 10 times the mass of the multi-walled carbon nanotubes dropwise at 4 mL / min, continuing to stir for 10 to 20 min, washing with deionized water for 3 to 8 times, and vacuum drying at 70° C. for 10 to 15 h to obtain carbon nanotubes loaded with nanosilver; (5) The carbon nanotube-loaded nanosilver and modified polypropylene are mixed in a mass ratio of 10:0.5-1.5, heated to 170-188° C., melt blended at a speed of 15-30 rpm for 10-20 min, and then annealed and extruded to obtain antistatic and antibacterial modified polypropylene particles.

2. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The dripping rate of step (1) is 1 to 3 mL / min.

3. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The mass ratio of the deionized water, hydrogen peroxide and 3-bromo-4-vinylpyridine in step (1) is 15:8-11:2.5-3.

5.

4. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The molecular weight of step (2) is 4×10 3 Preparation method of carboxyl-terminated polypropylene: 4 The polypropylene and 95wt% nitric acid aqueous solution are mixed in a mass ratio of 1:4, heated to 110°C for reflux, stirred at 150-300rpm for 8h, cooled to room temperature, washed with water and acetone in turn until the pH of the washing solution is 6, and dried at 50-80°C for 7-10h to obtain the product.

5. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The molecular weight of step (2) is 4×10 3 The mass ratio of carboxyl-terminated polypropylene, hydroxylated 3-bromo-4-vinylpyridine, cyclohexanone, 2-chloro-1-methyliodopyridine and triethylamine is 1:2-3:50:2-3:

2.

6. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: Step (3) the block copolymer, cyclohexanone, ethyl bromide, molecular weight 9×10 4 The mass ratio of polypropylene and xylene is 0.3:6:0.6:8~10:50~100.

7. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The preparation method of the silver ammonia solution in step (4) is as follows: 2 wt% silver nitrate aqueous solution and 2 wt% ammonia aqueous solution are mixed in a mass ratio of 1:0.5, and then the pH value of the solution is adjusted to 11 with ammonia water, and the temperature is raised to 35-45° C. and mixed evenly.

8. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The vacuum degree of the vacuum drying in step (1), step (2) and step (4) is 0.2-1 kPa.

9. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The annealing process parameters of step (5) are as follows: temperature of 120-180° C., pressure of 270-370 MPa, and time of 80-150 min.

10. The method for preparing antistatic and antibacterial modified polypropylene particles according to claim 1, characterized in that: The process parameters of the extrusion granulation in step (5) are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the temperatures of the three sections and the die are 170, 180, 200, and 220° C. respectively, and the shear rate is 80-150 rpm.

Citation Information

Patent Citations

  • Antibacterial polypropylene block copolymer and preparation method thereof and modified material containing block copolymer

    CN103304755A

  • Polypropylene composite material with high light transmittance, hydrolysis resistance, bacteria resistance and mildew resistance and preparation method thereof

    CN112646273A

  • Quantitative analysis method for internal and external loading capacities of carbon nanotubes

    CN116929880A

  • Flame-retardant antibacterial composite polypropylene filter material and preparation method thereof

    US20210178303A1

  • Hydrogenated product of block copolymer, resin composition, and method for producing hydrogenated product of block copolymer

    US20240052084A1